Quantum states engineering in graphene nanoribbons - Kong, F (2023)
The new upcoming generation of quantum devices requires the creation of solid state systems that display prominent quantum properties. This search, which is intensifying, has allowed identifying excellent quantum systems in molecular magnets, defect centres, low-dimensional materials, among others. Most efforts are directed towards systems produced with a top-down approach, e.g. by exfoliation or shaping of two-dimensional materials. This, however, prevents achieving the precise atom-by-atom control of the morphology that is usually necessary for topological and quantum properties to emerge distinctively in experiments.